Writers of the Black Chicago renaissance - Tracy, Steven C. (Steven Carl), 1954- (Urbana : University of Illinois Press, 2011)
"This volume explores the contours and content of the Black Chicago Renaissance. A movement crafted in the crucible of rigid racial segregation in Chicago's "Black Belt" from the 1930's through the 1960's, its participants were also heavily influenced by--and influenced --the Harlem Renaissance and the Chicago Renaissance of white writers. Despite harsh segregation, black and white thinkers influenced one another particularly through their engagements with leftist organizations. In many ways, politically, racially, spatially, this was a movement invested in cross-pollination, change, and political activism, as much as literature, art, and aesthetics as it prepared the way for the literature of the Black Arts Movement and beyond. The volume begins with a look at Richard Wright, indisputably a central figure in the Black Chicago Renaissance with the publication of "Blueprint for Negro Writing." Wright sought to distance himself from what he considered to be the failures of the Harlem Renaissance, even as he built upon its aesthetic and cultural legacy. Subsequent chapters discuss Robert Abbott, William Attaway, Claude Barnett, Henry Blakely, Aldon Bland, Edward Bland, Arna Bontemps, Gwendolyn Brooks, Frank London Brown, Alice Browning, Dan Burley, Margaret Danner, Frank Marshall Davis, Katherine Dunham, Richard Durham, Lorraine Hansberry, Fenton Johnson, John Johnson, Marian Minus, Williard Motley, Marita Bonner, Gordon Parks, John Sengstacke, Margaret Walker, Theodore Ward, Frank Yerby, Black newspapers, the Chicago School of Sociologists, the Federal Theater Project, Black Music, and John Reed Clubs"--
Cover -- Title Page -- Copyright -- Contents -- Acknowledgments -- Introduction Steven C. Tracy -- Robert S. Abbott Charlene Regester -- William A. Attaway Richard Yarborough -- Claude A. Barnett Bill V. Mullen -- Henry Lowington Blakely II Lovalerie King -- Alden Bland Joyce Hope Scott -- Edward Bland Lawrence Jackson -- Marita Bonner (Occomy) Kimberly N. Ruffin -- Gwendolyn Brooks Stephen Caldwell Wright -- Frank London Brown Michael D. Hill -- Alice C. Browning Bill V. Mullen -- Dan Burley Kimberly Stanley -- Margaret Esse Danner Keith D. Leonard -- Frank Marshall Davis Kathryn Waddell Takara -- Richard Durham Patrick Naick -- Lorraine Hansberry Lisbeth Lipari -- Fenton Johnson James C. Hall -- John H. Johnson Jamal Eric Watson -- "Mattie" Marian Minus Donyel Hobbs Williams -- Willard Motley Alan M. Wald -- Gordon Parks Elizabeth Schultz -- John Sengstacke Jamal Eric Watson -- Margaret Walker Maryemma Graham -- Theodore Ward Alan M. Wald -- Richard Wright Robert Butler -- Frank Garvin Yerby James L. Hill -- Black Writers and the Federal Theatre Project Angelene Jamison-Hall -- African American Music in Chicago during the Chicago Renaissance Robert H. Cataliotti -- The Black Press and the Black Chicago Renaissance Zoe Trodd -- The Chicago School of Sociology and the Black Chicago Renaissance William R. Nash -- John Reed Clubs/League of American Writers James Smethurst -- Materials for Further Study Steven C. Tracy -- Contributors -- Index.
Bibliographic Level Mode of Issuance: Monograph
English
Includes bibliographical references and index.
Description based on print version record.
Keywords: American literature -- Illinois -- Chicago -- History and criticism; American literature -- 20th century -- History and criticism; American literature -- African American authors -- History and criticism; Chicago (Ill.) -- Intellectual life -- 20th century